Orangutans (Pongo spp.) have deeper, more efficient sleep than baboons (Papio papio) in captivity. Issue 3 (7th March 2015) - Samson, David R.; Shumaker, Robert W.
ABSTRACT The nightly construction of arboreal sleeping platforms or "nests" has been observed among every great ape population studied to date. However, this behavior has never been reported in any other nonhuman primate and comparisons between ape and monkey sleep illuminate the link between sleeping substrates, positional behavior, and sleep efficiency. Here, we compare sleep depth and efficiency and night‐time positional behavior between a large‐bodied cercopithecoid (Papio papio) and a large‐bodied hominoid (Pongo spp.) at the Indianapolis Zoo. We used infrared videography to assess nightly sleep and awake behavioral states, gross body movements, and postures in baboons (N = 45 nights) and orangutans (N = 128 nights). We calculated the total waking time, total sleep time, sleep fragmentation (the number of brief awakenings ≥2 min/h), sleep motor activity (number of motor activity bouts per hour), sleep efficiency (sleep duration/time in bed), and percentage of time spent in each posture. By every measure, orangutans experienced overall deeper, more efficient sleep. Baboons were more likely to sleep in guarded, upright positions (weight bearing on their ischial callosities) and never opted to use additional materials to augment sleep environments, whereas orangutans slept in insouciant, relaxed positions on constructed sleeping materials. Our results suggest that relaxed sleeping postures may have been enabled by sleeping platforms as a behavioral facilitator to sleep, which could have allowed for greater sleep depth and next‐day cognitive capacities in both great apes and hominins. Am J Phys Anthropol 157:421–427, 2015. © 2015 Wiley Periodicals, Inc.